Development and standardization of Assamese photo articulation test - Koyel Das; Suman Kumar; Ruchira Mukherjee; Deepanshi Vaish; Dinesh Bhatia; Henry B. Nongrum (Journal of Child Language Acquisition and Development, 2023)
The articulation development follows an orderly sequence and it advances with the increase in age. Developmental articulation errors like simplification of one sound by another may occur and be accepted with the developmental period. Articulatory abilities and speech sound acquisition in Assamese has not been studied so far as per available literature and also there is no standard measure to evaluate articulation skills in Assamese-speaking children thus there is a need to develop and standardize articulation test in Assamese. The present study aimed to develop and standardize the Photo Articulation Test in Assamese by establishing norms of mastery of phonemes in typically developing Assamese-speaking children in the age range of 3-7 years. A total of 240 typically developing Assamese-speaking children were considered participants in this study from different districts of the state of Assam in North-Eastern India. Participants were equally divided into 8 age groups with equal gender distribution and with an age interval of six months in each group. The tool was developed in six stages i.e., Selection of words, Familiarization of the words, Preparation of the final list, Selection of pictures, Test administration, Scoring, and Statistical Analysis. Mastery of the respective phonemes was determined by 100% accuracy using PCC (Percentage Correct Scores), age and gender effect, error patterns, acquisition of clusters were also inquired into. The collected data were analyzed descriptively to find out the Mean Articulatory Score, Mean Score, and statistical analysis was done by using SPSS version 25.0. It may be concluded that among the phonemes of the Assamese language, the stops, glides, bilabials, and velars were the sounds achieved at a very early age along with glottal fricatives and affricates. Comparing the present study with the Western and Indian studies, most of the findings are well correlated and agrees with the findings of the present study. Thus, it may be inferred that the developed Photo Articulation Test may be a useful clinical tool for the assessment and therapeutic management of speech sound disorders (articulation and phonological disorders) in the Assamese population.